2003
DOI: 10.1016/s0028-3932(02)00126-4
|View full text |Cite
|
Sign up to set email alerts
|

Word-category specific deficits after lesions in the right hemisphere

Abstract: A speeded lexical decision task was used to investigate word-category deficits in patients suffering from lesions in the right hemisphere and in neurological controls without cortical lesion. In all patients from one group (n = 12), the right frontal lobe was affected causing a left-sided hemiparesis. In the second group (n = 6), lesions primarily affected areas in the right inferior temporo-occipital lobes. Patients with motor deficits due to lesions in the spinal cord or in the periphery served as neurologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 153 publications
(90 citation statements)
references
References 49 publications
6
80
0
4
Order By: Relevance
“…Some neuropsychological work reporting category-specific semantic deficits have already been mentioned in previous sections (e.g., Gainotti, 2004;Warrington & McCarthy, 1987). Data from stroke patients with lesions in inferior frontal or temporal lobes indicate a double dissociation between processing action verbs and object-related nouns (A. R. Damasio & Tranel, 1993;Daniele et al, 1994;Fazio et al, 2009;Gainotti, 2004;Miceli, Mazzucchi, Menn, & Goodglass, 1983;Neininger & Pulvermüller, 2003). Action verbs processing is also impaired specifically in patients with degenerative brain diseases affecting the motor system or its direct vicinity, including motor neuron disease (Bak, O'Donovan, Xuereb, Boniface, & Hodges, 2001), Parkinson's disease (Boulenger et al, 2008;Cotelli et al, 2007) and the frontal variant of frontotemporal dementia (Cotelli et al, 2006).…”
Section: Functional Relevancementioning
confidence: 91%
“…Some neuropsychological work reporting category-specific semantic deficits have already been mentioned in previous sections (e.g., Gainotti, 2004;Warrington & McCarthy, 1987). Data from stroke patients with lesions in inferior frontal or temporal lobes indicate a double dissociation between processing action verbs and object-related nouns (A. R. Damasio & Tranel, 1993;Daniele et al, 1994;Fazio et al, 2009;Gainotti, 2004;Miceli, Mazzucchi, Menn, & Goodglass, 1983;Neininger & Pulvermüller, 2003). Action verbs processing is also impaired specifically in patients with degenerative brain diseases affecting the motor system or its direct vicinity, including motor neuron disease (Bak, O'Donovan, Xuereb, Boniface, & Hodges, 2001), Parkinson's disease (Boulenger et al, 2008;Cotelli et al, 2007) and the frontal variant of frontotemporal dementia (Cotelli et al, 2006).…”
Section: Functional Relevancementioning
confidence: 91%
“…Especially the double dissociation in the processing of animal and tool knowledge [e.g., Buxbaum and Saffran, 2002] and in processing object-nouns and action verbs [e.g., Neininger and Pulvermü ller, 2003] provide strong evidence that the cortical systems necessary for processing visually based conceptual-perceptual knowledge and action knowledge differ. In addition, recent studies showed that motor cortex degeneration in motor neuron disease leads to a specific impairment of action words and concepts [Bak et al, 2001[Bak et al, , 2006, frontopartietal lesion associated with apraxia degrades object utilization knowledge more strongly than other conceptual aspects of object understanding [Buxbaum and Saffran, 2002], focal lesion in the motor cortex selectively impairs action word processing [e.g., Neininger and Pulvermü ller, 2003], and Parkinson's disease is also accompanied by a specific deficit in processing action verbs [Boulenger et al, 2008]. Although these studies are consistent with the notion of distributed semantic circuits with distinct topographies [for discussion, see Neininger and Pulvermü ller, 2003], they address relatively large semantic and conceptual domains (animal/tool, object/ action, noun/verb), whereas this study focused on more fine-grained distinctions (e.g., action subtypes).…”
Section: Category-specific Semantic Activation Clusters and The Effecmentioning
confidence: 99%
“…In addition, recent studies showed that motor cortex degeneration in motor neuron disease leads to a specific impairment of action words and concepts [Bak et al, 2001[Bak et al, , 2006, frontopartietal lesion associated with apraxia degrades object utilization knowledge more strongly than other conceptual aspects of object understanding [Buxbaum and Saffran, 2002], focal lesion in the motor cortex selectively impairs action word processing [e.g., Neininger and Pulvermü ller, 2003], and Parkinson's disease is also accompanied by a specific deficit in processing action verbs [Boulenger et al, 2008]. Although these studies are consistent with the notion of distributed semantic circuits with distinct topographies [for discussion, see Neininger and Pulvermü ller, 2003], they address relatively large semantic and conceptual domains (animal/tool, object/ action, noun/verb), whereas this study focused on more fine-grained distinctions (e.g., action subtypes). However, neuropsychological work also showed that the areas found active for the more fine-grained semantic subcategories play a critical role in their processing.…”
Section: Category-specific Semantic Activation Clusters and The Effecmentioning
confidence: 99%
“…Motor schemata would thus constitute an integral part of semantic knowledge of the word. This hypothesis might lead us to predict that the effects induced by TMS during action word production should be lateralized to the left hemisphere (but see Neininger & Pulvermüller, 2003, for evidence that right hemisphere damage may lead to difficulties in action word production).…”
Section: What Kinds Of Representations In Motor Cortex Are Associatedmentioning
confidence: 99%